Industrial Cd-Contaminated Soil Bioaugmented with Absidia cylindrospora: Influence on the Mineralogical Speciation of Cadmium: Insight on Fungal Influence in Cadmium Mineralogical Speciation in a Contaminated-Soil Experiment. Issue 10 (30th October 2020) - Albert, Quentin; Leleyter, Lydia; Lemoine, Mélanie; Heutte, Natacha; Sage, Lucile; Garon, David; Baraud, Fabienne
Abstract: Nowadays, trace metal contamination of soils is a worldwide concern. In the soil, the trace metals are distributed within different mineralogical fractions, which influence the transfers and the bioavailability, then the associated toxic risk. This study aims to investigate how the development of selected fungal mycelium influences the mineralogical speciation of cadmium. In a microcosm experiment with an industrial soil contaminated by various metal, including Cd, bioaugmentation experiments with the fungus Abisdia cylindrospora were conducted. A. cylindrospora showed a good development in the microcosm. Sequential extraction procedure highlighted the decrease of the potentially available fraction (5%) after 20 days of incubation. Most of the variations occur in the reducible and the oxidable fractions.